The conquest of the text by means of the combination of didactic and literary methods - Cervantes Almaguer, Diana de la Caridad (2018)
The article proposes a guide for the study of the poem Dos milagros, by José Martí, from an integrating perspective, in the combination of some of the known methods for literary analysis, both from the Didactics and from Literature. His basic assumption is the need to understand the meaning of social action in the context of the world, in this case from the Martian thought that is expressed, in all his work with a unique genius in his time. In the research that served as the basis for this article, the qualitative method of text analysis was used, which consists in analyzing the discourse and discovering the author’s intension from the hermeneutic and its relationship with other texts by the author himself? The proposal is based on the cognitive, communicative and sociocultural approaches, passing through the appropriate levels for the achievement of understanding, which also facilitates reflection on points of convergence and divergence of the text with modernist aesthetics and humanist validity of Martian thought.